Consciousness in "Don Quijote": Cervantes' contribution to the cognitive science of his time - Jaén Portillo, Isabel (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
Cervantes provides in Don Quixote a portrayal of human consciousness that highlights the connection between body, mind, and environment. While his portrayal is in line with the ideas of his time about the cognitive and emotional processes of human consciousness and its development, Cervantes' contribution to the cognitive science of his time rests on his creation of a "laboratory" or "live" demonstration of these processes and the impact they have on the individual and his social context. Sancho personifies the central themes in Cervantes' representation of human consciousness: the development of our rational faculties and control of our passions, via the acquisition of adequate habits of body and mind, and the acknowledgement of our abilities and limitations. Through Sancho, Cervantes brings us a complex and dynamic prototype of literary consciousness that inaugurates the powerful tool of psychological exploration that constitutes the novel.
Keywords: affects; brute; Cervantes; cognitive; consciousness; development; emotional; faculties; fiction; Huarte; human; humors; imagination; judgment; memory; novel; passions; rational; Sabuco; Sancho; Vives